Association Between Weather and Physical Activity in Baltimore Teens. (January 2013) - O'Neill, Allison H.; Lee, Sunmin; Yan, Alice; Voorhees, Carolyn C.
Previous studies have suggested that environmental characteristics such as weather may affect physical activity (PA) patterns; however, this association has not been studied in urban teenagers. PA data (measured by accelerometry) from 331 predominately urban, African American (70%) high school students from the Baltimore Active Living Teens Study were analyzed. Daily temperature and precipitation were significantly associated with PA. After adjusting for age, race, gender, and maternal education, for every 10°F increase, average moderate PA increased by 2.5 min (95% confidence interval [CI] = [0.5, 4.6]). Days with precipitation had on average 0.30 fewer minutes of vigorous PA (95% CI = [0.03, 0.56]) compared with days without precipitation. There were no significant associations between Air Quality Index or hours of daylight and PA. In conclusion, weather was associated with adolescents' PA, which suggests a need for a more diverse array of PA options not affected by weather.